Deformation induced precipitation of nano-particles in an Mg88Co5Y7 alloy. (15th April 2016) - Peng, Z.Z.; Shao, X.H.; Jin, Q.Q.; Li, C.H.; Ma, X.L.
Abstract: The nano-particles precipitated along basal and non-basal dislocation lines in an Mg88 Co5 Y7 (at.%) alloy during compression at 200 °C are observed. Aberration-corrected scanning transmission electron microscopic studies indicate that the nano-precipitate, with approximately 10 nm in diameter, has a face-centered cubic structure ( a = 0.523 nm). The nano-precipitate and Mg matrix exhibit an orientation relationship of (111)fcc ||(0001)Mg and 1 1 ̅ 0 fcc | | 2 1 ̅ 1 ̅ 0 Mg . We propose that hot compression-induced dislocations should be responsible for activating the atomic motion of solutes and succedent precipitation. The present study indicates that segregation of supersaturated solutes along the defects should be considered in Mg alloys upon deformation at medium temperatures. Graphical abstract: